(untitled) (Revista horizonte, 2013)
High levels of sedentary and overweight Chilean population, have positioned the country as one of the least active in the world. The objective of this research is to compare the fitness cohort of students of Pedagogy in Physical Education of the Universidad Autónoma de Chile, Temuco campus, from the evidence introduced by the Ministry of Education. The methodology considered a non experimental, descriptive, comparative, transversal, with a quantitative approach. The sample was selected on probabilistic criteria, which includes a total of 239 students distributed in males (n = 181) and females (n = 58), those in the range of 18 and 31, reaching average 22. The results reflect a more favorable nutritional status of the cohorts 2012 and 2011 compared to previous cohorts, who demonstrate a trend towards overweight, regarding structural and functional aspects of fitness cohorts 2012 and 2009 reach the best records in relation to other students analyzed.